2014
DOI: 10.3748/wjg.v20.i15.4167
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in colorectal cancer risk and clinical outcome

Abstract: Colorectal cancer (CRC) has an apparent hereditary component, as evidenced by the well-characterized genetic syndromes and family history associated with the increased risk of this disease. However, in a large fraction of CRC cases, no known genetic syndrome or family history can be identified, suggesting the presence of "missing heritability" in CRC etiology. The genome-wide association study (GWAS) platform has led to the identification of multiple replicable common genetic variants associated with CRC risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…This is essential for the suppression of metastasis, and the survival rate significantly improves with high levels of KISS1. 29 It is estimated that these genetic syndromes represent about 10% of all cases of colorectal cancer; however about 25% of cases the familial history contributes to an increased risk of developing colorectal cancer in the absence of these genetic syndromes 30 . Factors such as history of ulcerous colitis, Chron's disease, personal history of polyposis, colon, rectal, ovarian, endometrium, breast cancer, and diabetes mellitus are related to a 30-50% greater risk of developing colorectal cancer, and about 75% of the malignant tumors of the colon and rectum are presented without related any of these risk factors; The relationship between hyperplastic polyposis and cancer is controversial.…”
Section: Epidemiologymentioning
confidence: 99%
“…This is essential for the suppression of metastasis, and the survival rate significantly improves with high levels of KISS1. 29 It is estimated that these genetic syndromes represent about 10% of all cases of colorectal cancer; however about 25% of cases the familial history contributes to an increased risk of developing colorectal cancer in the absence of these genetic syndromes 30 . Factors such as history of ulcerous colitis, Chron's disease, personal history of polyposis, colon, rectal, ovarian, endometrium, breast cancer, and diabetes mellitus are related to a 30-50% greater risk of developing colorectal cancer, and about 75% of the malignant tumors of the colon and rectum are presented without related any of these risk factors; The relationship between hyperplastic polyposis and cancer is controversial.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although the risk of CRC increases with age, the incidence of both hereditary and sporadic forms is increasing gradually per year in individuals younger than 50 years (34). Genetic, ethnic, environmental, and especially dietary factors are important determinants of colorectal carcinogenesis (35,36). CRC most often begins as precancerous polyps, and it is assumed that a malignant transformation takes approximately 10-15 years to occur (7).…”
Section: Colorectal Cancermentioning
confidence: 99%
“…To date, the identification of low‐penetrance CRC susceptibility variants has largely been accomplished by population‐based case‐control GWAS. While these studies have identified over 40 independent low‐penetrance variants from different populations, the proportion of genetic risk that they explain is modest and incomplete . Given that heritable factors are estimated to account for 12 to 35% of the risk for developing CRC, it has been proposed that the remainder of risk comes from rare variants, copy number variants, gene‐gene interactions, gene‐environment interactions and parent‐of‐origin effects—though overestimates of heritability are also a possible explanation for the missing heritability …”
mentioning
confidence: 99%